Synthesis of Bio-diesel and Bio-lubricant by transesterification of vegetable oil with lower and higher alcohols over heteropolyacids supported by clay (K-10) - Bokade, Vijay V.; Yadav, G. D. (Process Safety and Environmental Protection, 2007)
{The use of different lower and higher alcohols viz; methanol, ethanol, n-propanol and n-octanol, for the synthesis of methyl, ethyl, propyl and octyl fatty acid esters by transesterification of vegetable oil (triglycerides) with respective alcohols also known as `Bio-diesel' and `Biolubricants' was studied in detail. The reactions were carried out in a batch process. The activity with different supports like clay (K-10), activated carbon, ZSM-5, H-beta and TS-1 were compared. The superacids (heteropolyacids, HPA) viz; Dodeca-Tungstophosphoric acid [
Keywords: coprecipitation; lithium aluminate; Microemulsion; Nanoparticles; sol-gel; Surfactants

Synthesis of pharmaceutical intermediates by toluene benzylation over heteropoly acids on different support - Bokade, Vijay V.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{Selective formation of pharmaceutical intermediates like diphenylmethane, dimethyl-diphenylmethane, benzyl toluene and benzoic acid by liquid phase, toluene benzylation with benzyl chloride as a benzylating agent, was systematically studied over plane clay (K-10, montmorillonite), plane H-Beta, plane MFI structured titanosilicate (TS-1) and heteropoly acids [
Keywords: heteroassembly; nanoplates; polyfunctional capping agents; shape selective synthesis of gold-silver nanostructures; surface confinement

Toluene alkylation with methanol to p-xylene over heteropoly acids supported by clay - Bokade, Vijay V.; Deshpande, Suvarna S.; Patil, R.; Jain, S.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{The alkylation of toluene with methanol for the selective formation of p-xylene was systematically studied. Very few studies have been reported on the use of superacids such as heteropolyacids on cheap supports, such as clay. This article deals with the use of different heteropoly acids (HPAs), viz, Dodeca-Tungstophosphoric acid [
Keywords: co-crystalline; p-xylene; toluene alkylation; ZSM-12; ZSM-5